Education, Growth, and Redistribution in the Presence of Capital Flight - Debajyoti Chakrabarty; Areendam Chanda; Chetan Ghate (Max Planck Institute of Economics, 2006)
We construct an overlapping generations model to study the effect of capital controls on human capital investments and the incidence of redistributive politics in a growing economy. We argue that the conventional wisdom linking higher capital controls to lower growth is reproduced only when an economy is sufficiently developed. For under-developed countries, higher capital controls are beneficial for human capital accumulation suggesting that the wisdom does not apply. In an augmented version of the model, we show that a modern sector, characterized by positive levels of investment in education, may not exist unless capital controls are sufficiently high. In particular, higher capital controls make it feasible for a modern sector to exist by lowering the threshold income level required by workers to invest in human capital. These results are consistent with recent evidence suggesting that capital account liberalization positively affects growth only after a country has achieved a certain threshold level of absorptive capacities.
Keywords: D33; E62; F21; O19; O40; 330; Capital Flight; Economic Growth; Human Capital; Income Distribution; Long Term Capital Movements; Optimal Taxation; Kapitalflucht; Wirtschaftswachstum; Overlapping Generations; Einkommensumverteilung; Humankapital; Optimale Besteuerung; Theorie